New invertebrate vectors of Okadaic acid from the North Atlantic Waters - Portugal (Azores and Madeira) and Morocco - Silva, Marisa (2016)
Okadaic acid and its analogues are potent phosphatase inhibitors that cause Diarrheic Shellﬁsh Poisoning (DSP) through the ingestion of contaminated shellﬁsh by humans. This group of toxins is transmitted worldwide but the number of poisoning incidents has declined over the last 20 years due to legislation and monitoring programs that were implemented for bivalves. In the summer of 2012 and 2013, we collected a total of 101 samples of 22 different species that were made up of benthic and subtidal organisms such echinoderms, crustaceans, bivalves and gastropods from Madeira, São Miguel Island (Azores archipelago) and the northwestern coast of Morocco. The samples were analyzed by UPLC-MS/MS. Our main objective was to detect new vectors for these biotoxins. We can report nine new vectors for these toxins in the North Atlantic: Astropecten aranciacus, Arbacia lixula, Echinaster sepositus, Holothuria sanctori, Ophidiaster ophidianus, Onchidella celtica, Aplysia depilans, Patella spp., and Stramonita haemostoma. Differences in toxin contents among the species were found. Even though low concentrations were detected, the levels of toxins that were present, especially in edible species, indicate the importance of these types of studies. Routine monitoring should be extended to comprise a wider number of vectors other than for bivalves of okadaic acid and its analogues.